2021
DOI: 10.19044/ejes.v8no4a53
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and Challenges of Online Teaching During the COVID-19 Pandemic at Rundu Campus of the University of Namibia

Abstract: This paper presents the benefits and challenges of online teaching during the COVID-19 pandemic experienced by educators at the Rundu Campus of the University of Namibia. Researchers used a structured interview guide to collect data from 14 conveniently selected lecturers from a population of 65. Findings of the study indicate that the benefits of using online teaching and learning include flexibility, ability to teach large classes; increased interaction and engagement between lecturers and students; and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In this sense, a study in Ethiopia highlights students’ dissatisfaction with poor Internet connectivity. A similar study in Tanzania highlighted the difficulties faced by teachers and students in using the online learning platform effectively [ 31 , 32 ]. These barriers have prevented a smooth transition to DE.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…In this sense, a study in Ethiopia highlights students’ dissatisfaction with poor Internet connectivity. A similar study in Tanzania highlighted the difficulties faced by teachers and students in using the online learning platform effectively [ 31 , 32 ]. These barriers have prevented a smooth transition to DE.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…In response to the mandatory social isolation due to COVID-19, teachers and students had to respond rapidly and significantly to changing their teaching and learning approach, regardless of their familiarity with online education or their technological prowess [15,16]. Indeed, the key challenges and benefits of online teaching are evident in a higher education setting [17][18][19]; however, there is limited evidence in the literature particularly regarding teaching narratives from educators' perspectives within the context of a time-constrained block teaching mode, as we have encountered at Victoria University's First Year College.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the prevalence of using the internet as an online learning resource, students' academic results have improved (Siraj et al, 2015). Mbongo et al (2021) revealed that adopting online teaching and learning has advantages such as flexibility, teaching vast courses, and enhanced contact and engagement between lecturers and students, all of which were made possible by the internet. Hence, the internet surfing has an impact on students' academic standards.…”
Section: Introductionmentioning
confidence: 99%